Behaviour of Listeria monocytogenes in raw milk Cantal type cheeses during cheese making, ripening and storage in different packaging conditions. (August 2015) - Chatelard-Chauvin, C.; Pelissier, F.; Hulin, S.; Montel, M.C.
Abstract: The aim of this study was to run challenge tests to investigate the behaviour of Listeria monocytogenes in raw milk Cantal type uncooked pressed cheeses throughout the cheese process and during storage in different packagings (stretch film, vacuum packs and kraft paper) at 6 °C during two-thirds of the storage period, then at 10 °C; for kraft paper the last five days were at 15 °C. Whatever the weight of the cheese (10 or 40 kg), L. monocytogenes only increased during the first 24 h of cheese making and decreased significantly in both cores and rinds during ripening at 9 °C from day 45 to day 360. In cores, decay rate can depend on milk properties and in our experiment were associated with high levels of lactate and acetate during ripening. The decrease continued significantly in the cores during storage in all three packagings, more rapidly than during ripening. The populations of the pathogen were usually similar whatever the packaging. In rind, L monocytogenes decreased most significantly during storage in kraft paper; after 45 days of storage the counts were significantly lower in kraft paper than under vacuum whereas Gram positive non lactic acid bacteria and yeasts were at higher counts. The low a w (<0.90) in the rinds of kraft wrapped portions may be responsible for this decrease. High pH (6 < pH < 8) in the rind during ripening and storage did not hinder the decrease. This study provides data for developing models of L. monocytogenes inactivation and for attributing by food safety authorities the appropriate category for Cantal type cheeses with regard to European regulation. Highlights: Long ripening times for raw milk Cantal type cheeses lead to decrease in L. monocytogenes . Lactic acid and acetic acid involved in inhibition in cheese cores. Sharp decrease in L. monocytogenes in the cheese cores during storage in all three packaging conditions. Low a w in rinds may contribute to the decrease in L. monocytogenes in kraft wrapped portions. High pH in rinds does not hinder L. monocytogenes decrease.